2009
DOI: 10.2106/jbjs.h.01512
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial Aspects of Disabling Musculoskeletal Pain

Abstract: Psychosocial factors are important determinants of pain intensity and disability in patients with disabling musculoskeletal pain. The psychosocial aspects of disabling musculoskeletal pain include cognitive (e.g., beliefs, expectations, and coping style), affective (e.g., depression, pain anxiety, heightened concern about illness, and anger), behavioral (e.g., avoidance), social (e.g., secondary gain), and cultural factors. The effectiveness of cognitive behavioral therapy and other treatments that address the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
156
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 244 publications
(160 citation statements)
references
References 38 publications
3
156
0
1
Order By: Relevance
“…Psychosocial factors have been shown to influence baseline scores on many commonly used upper extremity orthopaedic outcome scales [6,17,23,25,26,28,33]. Higher levels of psychological distress also correlate with inferior patient-reported outcomes after surgical intervention in other areas of orthopaedics [4,16,22,31,32,34].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Psychosocial factors have been shown to influence baseline scores on many commonly used upper extremity orthopaedic outcome scales [6,17,23,25,26,28,33]. Higher levels of psychological distress also correlate with inferior patient-reported outcomes after surgical intervention in other areas of orthopaedics [4,16,22,31,32,34].…”
Section: Discussionmentioning
confidence: 99%
“…We [23] and others [6,28] have reported that greater distress is associated with lower preoperative self-assessment scores in patients with shoulder pathology, but to our knowledge, this is the first investigation to consider the relationship of distress and outcome scores after arthroscopic rotator cuff repair. Results from populations undergoing total joint arthroplasty [16], surgery for degenerative spine conditions [19,31,32], hip arthroscopy [22], or upper extremity surgery [33] have suggested that for distressed patients, higher levels of pain and lower levels of function often persist after surgical intervention. It is possible that our results here differ from most prior studies because of an underlying difference in the nature of rotator cuff disease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Orthopaedic surgeons expect fewer symptoms and limitations when surgery improves motion, when radiographic arthritis is less severe, and when a sutured rotator cuff defect heals. We are surprised to find that greater motion, more severe radiographic arthritis, and persistent defects after surgery are not always associated with reductions in symptoms and functional limitations [4]. We are puzzled by the ability of sham surgery and injection to relieve symptoms [5].…”
mentioning
confidence: 99%
“…With more routine use of PROMs, surgeons will want to pay more attention to the factors that have the strongest influence on these scores: Stress, distress, and ineffective coping strategies [4]. The influence of mindset and circumstances on musculoskeletal illness is evident to orthopedic surgeons of all subspecialties.…”
mentioning
confidence: 99%